Temperature‐dependent small signal performance of GaN‐on‐diamond HEMTs. (14th May 2019) - Chen, Yongbo; Xu, Yuehang; Zhou, Jianjun; Kong, Yuechan; Chen, Tangsheng; Zhang, Yong; Yan, Bo; Xu, Ruimin
Abstract: This paper presents the temperature dependence of small signal performance of GaN‐on‐diamond high electron mobility transistors (HEMTs) at an ambient temperature range from 0°C to 125°C. The temperature influence on the parasitic resistances together with the intrinsic parameters is investigated, and the temperature coefficients of these parameters are extracted from measured data. For comparison, a GaN‐on‐SiC device is also investigated. These results are important for the development and application of the GaN‐on‐diamond HEMT technology.